The Effects of Drug Control Policies on Individual and Community Health for People of Color: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The United States has a complex system of laws and policies that attempt to regulate the distribution, manufacture, and use of a variety of non-legal drug substances as part of its overall criminal justice system. Laws regarding drug use have disproportionately impacted individuals and communities of color at every step of the journey through the criminal justice system, including arrest, conviction, sentencing, and incarceration. These disparities have clear outcomes for both individual and community health. To examine the effects of drug control policies on the health of individuals and communities of color, the Roundtable on the Promotion of Health Equity held a workshop on October 8, 2018, in Washington, DC. This publication summarizes the presentations and discussions of the workshop.
Keywords: Health and Medicine

Behavioral Economics and the Promotion of Health Among Aging Populations: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
There has been a significant increase in research applying behavioral economics and related behavioral science to health. The National Academies of Sciences, Engineering, and Medicine convened a workshop June 4–5, 2018, to discuss behavioral economics research with the goal of extending such research to be of benefit to older and middle-aged adults. The goals of the workshop were (1) to share knowledge about successful applications; (2) to encourage investigations that will deepen understanding of the specific conditions, people, and contexts for which such applications are more and less effective; and (3) to identify the mechanisms underlying the interventions. Specifically, there was a focus on considering interventions that could generate long-term benefits in areas of interest to the National Institute on Aging, such as decreasing sedentary behavior, promoting volunteering and social engagement, improving medical regimen adherence, and reducing inappropriate use of opioids and using opioids when medically necessary. This publication summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences

Pain Management for People with Serious Illness in the Context of the Opioid Use Disorder Epidemic: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The United States is facing an opioid use disorder epidemic with opioid overdoses killing 47,000 people in the U.S. in 2017. The past three decades have witnessed a significant increase in the prescribing of opioids for pain, based on the belief that patients were being undertreated for their pain, coupled with a widespread misunderstanding of the addictive properties of opioids. This increase in prescribing of opioids also saw a parallel increase in addiction and overdose. In an effort to address this ongoing epidemic of opioid misuse, policy and regulatory changes have been enacted that have served to limit the availability of prescription opioids for pain management.
Keywords: Health and Medicine

Exploring Tax Policy to Advance Population Health, Health Equity, and Economic Prosperity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine’s Roundtable on Population Health Improvement has been focused on the subject of dependable resources for population health since its inception in 2013. On December 7, 2017, the roundtable convened a workshop to explore tax policy as it relates to advancing population health, health equity, and economic prosperity. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Exploring Tax Policy to Advance Population Health, Health Equity, and Economic Prosperity: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
On December 7, 2017, the Roundtable on Population Health Improvement held a 1-day workshop in Oakland, California, at The California Endowment Oakland Regional Office–Healthy Communities Center. The workshop featured presentations, panel discussions, and an exercise about tax policy as both an influence on health outcomes and a possible source of financing for population health activities; ranging from diabetes prevention to universal pre-kindergarten. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Nontechnical Strategies to Reduce Children's Exposure to Inappropriate Material on the Internet: Summary of a Workshop - National Research Council; Institute of Medicine (The National Academies Press, 2001)
In response to a mandate from Congress in conjunction with the Protection of Children from Sexual Predators Act of 1998, the Computer Science and Telecommunications Board and the Board on Children, Youth, and Families of the National Research Council and the Institute of Medicine established a committee of experts to explore options to protect children from pornography and other inappropriate Internet content. In June 2000, the Committee to Study Tools and Strategies for Protecting Kids from Pornography on the Internet and Their Applicability to Other Inappropriate Internet Content was established. Support for the committee's work came from the U.S. Department of Education, the U.S. Department of Justice, Microsoft Corporation, IBM, the W.K. Kellogg Foundation, and the National Research Council. The committee has been charged with exploring the pros and cons of different technology options and operational policies as well as nontechnical strategies that can help to provide young people with positive and safe online experiences. On December 13, 2000, the committee convened a workshop to provide public input to its work and focus on nontechnical strategies that could be effective in a broad range of settings (e.g., home, school, libraries) in which young people might be online. The overarching goal of this activity was to provide a forum for discussing the implications of this research with regard to policy and practice and identifying research needed to advance and inform policy and practice.
Keywords: Behavioral and Social Sciences

Measuring Recovery from Substance Use or Mental Disorders: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In February 2016, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore options for expanding the Substance Abuse and Mental Health Services Administration’s (SAMHSA) behavioral health data collections to include measures of recovery from substance use and mental disorder. Participants discussed options for collecting data and producing estimates of recovery from substance use and mental disorders, including available measures and associated possible data collection mechanisms. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics

Improving Access to High-Quality Mental Health Care for Veterans: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The mental and behavioral health care needs of Americans, including veterans, have substantially grown over the past few decades. As the nations largest provider of mental health care, the U.S. Department of Veterans Affairs (VA) faces some of the greatest challenges in meeting the mental health care needs of its population. These challenges are exacerbated by a shrinking mental health care workforce and provider shortages in low-income and rural communities. To address these challenges, and at the request of VA, the National Academies of Sciences, Engineering, and Medicine Forum on Mental Health and Substance Use Disorders held a public workshop on Improving Access to High-Quality Mental Health Care for Veterans to explore the U.S. landscape for mental health care services, including telehealth services. The workshop considered ways to improve veterans timely access to high-quality care for mental health conditions. In particular, it explored internal and external best practices for three critical needs for mental health access (known as tripartite access in VA): urgent/crisis, engagement, and sustained access. This proceedings document summarizes discussions at the workshop.
Keywords: Health and Medicine

A Population Health Perspective on Middle School Success: Activities, Programs, and Policies: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
On December 5, 2019, the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore the factors that affect the health and well-being of middle-school-aged adolescents. The workshop included presentations on the risk factors of poor physical, social, and emotional outcomes and their prevalence; the identification of resilience factors; current policies and programs designed to support middle school success and address issues of equity and financing as they apply to these; and how the health and human services sectors can support and align with the education sector to promote health and well-being in middle school. This publication summarizes the presentations and discussions that took place during the workshop.
Keywords: Health and Medicine

The Role of Nonpharmacological Approaches to Pain Management: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Pain is a leading cause of disability globally. The dramatic increase in opioid prescriptions within the past decade in the United States has contributed to the opioid epidemic the country currently faces, magnifying the need for longer term solutions to treat pain. The substantial burden of pain and the ongoing opioid crisis have attracted increased attention in medical and public policy communities, resulting in a revolution in thinking about how pain is managed. This new thinking acknowledges the complexity and biopsychosocial nature of the pain experience and the need for multifaceted pain management approaches with both pharmacological and nonpharmacological therapies.
Keywords: Health and Medicine

Civic Engagement and Civic Infrastructure to Advance Health Equity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
There is increasing evidence that civic participation - from voting to volunteering - is a social driver of health. The National Academies of Sciences, Engineering, and Medicine's Roundtable on Population Health Improvement convened a workshop to explore the links between civics and health; between measures of civic engagement and quantitative and qualitative measures of health equity; and the roles that civic infrastructure, narrative, and media play in shaping civic engagement. Presenters discussed voting along with other important dimensions of civic engagement; others include the ability to set agendas, shape how policies are implemented, communicate information, model civic behavior, and support the involvement and inclusion of other individuals and groups.
Keywords: Health and Medicine

Addressing the Rising Mental Health Needs of an Aging Population: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Existing systems are not prepared to provide the mental health care services needed by the growing population of older adults. The National Academies Forum on Mental Health and Substance Use Disorders hosted a public workshop in May 2023 to highlight the current state of mental health care for older adults, outline the challenges they face, and explore potential long-term strategies and solutions for addressing unmet mental health needs. Discussions emphasized information about wellness and prevention, social determinants of health in aging populations, the impact of workforce shortages and gaps, the need for supportive healthy communities, and strategies to promote positive mental health.This publication summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine

Defining and Evaluating In-Home Drug Disposal Systems For Opioid Analgesics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The proper disposal of unused or expired prescription drugs, particularly controlled substances such as opioids, may help to prevent serious risk of nonmedical use or overdose. In June 2023, the National Academies Forum on Drug Discovery, Development, and Translation hosted a hybrid public workshop to examine the scientific merit and practical implementation of drug disposal options to remove opioid analgesics from the home. Workshop participants considered potential strategies for encouraging and assessing the development and efficacy of in-home drug disposal systems that support the public health goal of mitigating the risk of nonmedical use or overdose associated with opioids.
Keywords: Health and Medicine

Improving the Health of Women in the United States: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The environment for women's health has changed over the last 25 years. Increased use of automobiles can lead to health risks from lack of physical activity. There has also been an increase in access to and consumption of unhealthy food. Other changes in the past 2 to 3 decades include the significant increase in the number of women who are heads of households and responsible for all aspects of a household and family. Many women now are also having children later in life, which poses interesting issues for both biology and sociology. The growing stress faced by women and the effect of stress on health and illness are issues that need a more comprehensive examination, as do issues of mental health and mental illness, which have been more common and thus increasingly prominent issues for U.S. women. In September 2015, the National Academies of Sciences, Engineering, and Medicine convened a workshop to shed light on important determinants, consequences, effects, and issues attending the relative disadvantage of women in the United States in comparison with women in other economically advanced nations. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Family-Focused Interventions to Prevent Substance Use Disorders in Adolescence: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Adolescence is a crucial period of life for the prevention of substance use disorders. Research has shown that early intervention can significantly reduce rates of substance use disorder in adulthood. To learn more about effective family-focused interventions in primary care settings for preventing substance use disorder, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on May 5-6, 2022. The proceedings from that workshop explores existing efforts to incorporate family-focused interventions into state health care policies. It also examines barriers to implementing such interventions as well as lessons learned from successful efforts to scale up these interventions.
Keywords: Behavioral and Social Sciences

Assessing 21st Century Skills: Summary of a Workshop - National Research Council (The National Academies Press, 2011)
The routine jobs of yesterday are being replaced by technology and/or shipped off-shore. In their place, job categories that require knowledge management, abstract reasoning, and personal services seem to be growing. The modern workplace requires workers to have broad cognitive and affective skills. Often referred to as "21st century skills," these skills include being able to solve complex problems, to think critically about tasks, to effectively communicate with people from a variety of different cultures and using a variety of different techniques, to work in collaboration with others, to adapt to rapidly changing environments and conditions for performing tasks, to effectively manage one's work, and to acquire new skills and information on one's own. The National Research Council (NRC) has convened two prior workshops on the topic of 21st century skills. The first, held in 2007, was designed to examine research on the skills required for the 21st century workplace and the extent to which they are meaningfully different from earlier eras and require corresponding changes in educational experiences. The second workshop, held in 2009, was designed to explore demand for these types of skills, consider intersections between science education reform goals and 21st century skills, examine models of high-quality science instruction that may develop the skills, and consider science teacher readiness for 21st century skills. The third workshop was intended to delve more deeply into the topic of assessment. The goal for this workshop was to capitalize on the prior efforts and explore strategies for assessing the five skills identified earlier. The Committee on the Assessment of 21st Century Skills was asked to organize a workshop that reviewed the assessments and related research for each of the five skills identified at the previous workshops, with special attention to recent developments in technology-enabled assessment of critical thinking and problem-solving skills. In designing the workshop, the committee collapsed the five skills into three broad clusters as shown below:
Keywords: Education

Improving the Health, Safety, and Well-Being of Young Adults: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
Young adults are at a significant and pivotal time of life. They may seek higher education, launch their work lives, develop personal relationships and healthy habits, and pursue other endeavors that help set them on healthy and productive pathways. However, the transition to adulthood also can be a time of increased vulnerability and risk. Young adults may be unemployed and homeless, lack access to health care, suffer from mental health issues or other chronic health conditions, or engage in binge drinking, illicit drug use, or driving under the influence. Young adults are moving out of the services and systems that supported them as children and adolescents, but adult services and systems—for example, the adult health care system, the labor market, and the justice system—may not be well suited to supporting their needs. Improving the Health, Safety, and Well-Being of Young Adults is the summary of a workshop hosted by the Board on Children, Youth, and Families of the Institute of Medicine (IOM) and the National Research Council (NRC) in May, 2013. More than 250 researchers, practitioners, policy makers, and young adults presented and discussed research on the development, health, safety, and well-being of young adults. This report focuses on the developmental characteristics and attributes of this age group and its placement in the life course; how well young adults function across relevant sectors, including, for example, health and mental health, education, labor, justice, military, and foster care; and how the various sectors that intersect with young adults influence their health and well-being. Improving the Health, Safety, and Well-Being of Young Adults provides an overview of existing research and identifies research gaps and issues that deserve more intensive study. It also is meant to start a conversation aimed at a larger IOM/NRC effort to guide research, practices, and policies affecting young adults.
Keywords: Health and Medicine

Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Reducing the Treatment Gap, Improving Quality of Care: Summary of a Joint Workshop by the Institute of Medicine and the Uganda National Academy of Sciences - Institute of Medicine (The National Academies Press, 2010)
Millions of people in sub-Saharan Africa suffer from mental, neurological, and substance use (MNS) disorders, and most do not have the resources to obtain treatment. The Uganda National Academy of Sciences and the Institute of Medicine hosted a workshop to discuss the state of care for MNS disorders in sub-Saharan Africa.
Keywords: Health and Medicine

Exploring Psychedelics and Entactogens as Treatments for Psychiatric Disorders: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Psychiatric illnesses - such as major depressive disorder, anxiety disorder, substance use disorder, and posttraumatic stress disorder (PTSD) - are widely prevalent and represent a substantial health burden worldwide. Yet, conventional medications for mental illnesses often fail to provide relief to patients' disruptive and disabling symptoms. Existing and emerging evidence that psychedelics (e.g., LSD and psilocybin) and entactogens (e.g., MDMA) may be useful as tools to alleviate mental illness has sparked a renaissance of interest by investigators, clinicians, drug developers, and patient advocates in recent years. While promising data on therapeutic efficacy has energized research and development, resolving the mechanisms of action will be important for optimizing the efficacy and safety of these medicines. Further, evaluating the effect of psychedelics and entactogens on mood and behavior comes with unique challenges still in need of resolution. These include unresolved questions relating to blinding, placebo and nocebo effects, and the impact of psychosocial contexts. In response to this renewed interest, the National Academies of Sciences, Engineering, and Medicine's Forum on Neuroscience and Nervous System Disorders convened a workshop on March 29-30, 2022. The workshop brought together a diverse group of stakeholders to explore the use of psychedelics and entactogens as treatments for psychiatric disorders. This Proceedings of a Workshop summarizes the presentations and discussions of the workshop.
Keywords: Health and Medicine

Exploring the Power of Youth Leadership in Creating Conditions for Health and Equity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Young people often engage and lead efforts to improve the social, economic, and environmental factors that influence the health and equity of communities and the nation. The National Academies Roundtable on Population Health Improvement hosted a hybrid public workshop in September 2023 at The California Endowment Center for Healthy Communities in Oakland, California to discuss the power of youth leadership in creating conditions for health and equity and the civic infrastructure and resources that support youth participation and leadership in change efforts.
Keywords: Health and Medicine